2017
DOI: 10.1097/mph.0000000000000707
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life (HR-QOL) and Chronic Health Conditions in Survivors of Childhood Acute Myeloid Leukemia (AML) with Down Syndrome (DS): A Report From the Children’s Oncology Group

Abstract: Survival rates for children with Down syndrome (DS) and acute myeloid leukemia (AML) are high; however, little is known regarding the health-related quality of life (HR-QOL) of these survivors. Individuals who survived ≥5 years following diagnosis of childhood AML were invited to complete parent or patient-report surveys measuring HR-QOL and chronic health conditions. Twenty-six individuals with DS had a median age at diagnosis of 1.8 years (range, 0.77-10.9) and median age at interview of 15 years (range 8.3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
1
13
0
3
Order By: Relevance
“…Previous reports on late effects in leukemia survivors with DS are sparse. A recent report from the Children's Oncology Group showed that 77% of AML survivors with DS reported at least 1 chronic medical condition compared with 50% of AML patients without DS . A report evaluating late cardiomyopathy in AML patients with and without DS showed no difference in the incidence of this condition .…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Previous reports on late effects in leukemia survivors with DS are sparse. A recent report from the Children's Oncology Group showed that 77% of AML survivors with DS reported at least 1 chronic medical condition compared with 50% of AML patients without DS . A report evaluating late cardiomyopathy in AML patients with and without DS showed no difference in the incidence of this condition .…”
Section: Discussionsupporting
confidence: 48%
“…A recent report from the Children's Oncology Group showed that 77% of AML survivors with DS reported at least 1 chronic medical condition compared with 50% of AML patients without DS. 29 A report evaluating late cardiomyopathy in AML patients with and without DS showed no difference in the incidence of this condition. 30 We also identified that children with DS and leukemia do not seem at higher risk for late cardiac conditions than those without DS despite the known increased incidence of cardiovascular malformations.…”
Section: Survivors Of Leukemia With Down Syndrome/goldsby Et Almentioning
confidence: 97%
“…Here, survivors of leukemia scored poorer on neuropsychological tests compared with leukemia‐free individuals with DS. The other studies compared HR‐QoL or self‐reported chronic conditions among leukemia survivors with DS and leukemia survivors without DS. Leukemia survivors with DS have lower HR‐QoL, more chronic conditions, and more severe chronic condition compared with leukemia survivors without DS.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their increased incidence of leukemia, only three studies of late effects focus on survivors with DS. DS survivors had poorer results on neuropsychological tests compared to leukemia‐free individuals with DS, have a lower health‐related quality of life (HR‐QoL), and more chronic diseases compared with leukemia survivors without DS. The limited knowledge about late effects among DS leukemia survivors is problematic because DS survivors constitute an important subgroup of individuals with childhood leukemia with distinct medical needs.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of this subtype is better compared to the other AML subtypes in children without Down syndrome . Also, the quality of life in AML survivors with Down syndrome appears similar to that of survivors of AML without Down syndrome …”
Section: Introductionmentioning
confidence: 75%